2022
DOI: 10.30901/2227-8834-2022-3-161-170
|View full text |Cite
|
Sign up to set email alerts
|

Conspectus of the genus <i>Juniperus</i> L. growing in Kazakhstan

Abstract: Background. The genus Juniperus L. is the most numerous in the family Cupressaceae Bartl. and includes about 75 species. There are from 7 to 10 species of this genus in Kazakhstan. All types of juniper are widely used in folk medicine and play an important ecological role. The purpose of our work was to study the current status, systematics and distribution of juniper species. This will help to clarify and expand the information on the current location of Juniperus species in Kazakhstan and will be used in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Similar to our results, Ghorbanzadeh et al (2021) reported that the PIC fluctuated between 0.26 and 0.47. Furthermore, Yermagambetova et al (2022) investigated Juniperus species from central Asia and found the PIC value varied between 0.077 and 0.662, with an average of 0.43. The genetic variation between Juniperus species is significantly influenced by the geographical region, the primer employed, and the plant species.…”
Section: Primer Namementioning
confidence: 99%
“…Similar to our results, Ghorbanzadeh et al (2021) reported that the PIC fluctuated between 0.26 and 0.47. Furthermore, Yermagambetova et al (2022) investigated Juniperus species from central Asia and found the PIC value varied between 0.077 and 0.662, with an average of 0.43. The genetic variation between Juniperus species is significantly influenced by the geographical region, the primer employed, and the plant species.…”
Section: Primer Namementioning
confidence: 99%
“…Species in the genus are widely distributed in dry foothills or at mid to high altitudes of Central Asian mountains, including Kazakhstan [2]. In Kazakhstan, the genus representatives are mainly found on dry mountain slopes and in alpine and subalpine belts [3,4]. The country has eight species of Juniperus, including J. communis L., J. sibirica Burgsd., J. x media Dmitr., J. pseudosabina Fisch.…”
Section: Introductionmentioning
confidence: 99%
“…This species can grow on a wide variety of substrates, from steep (up to 70°) rocky outcrops to nutrient-rich brown soils with a significant (up to 16%) humus content. This property plays an essential ecological role in water and soil protection, preventing destructive mudflows on mountain ranges [ 6 ]. Despite the wide distribution of this species in the region, a decrease in the number of natural populations has been observed.…”
Section: Introductionmentioning
confidence: 99%